Descemet Membrane Endothelial Keratoplasty - Complication and management of a single case for tissue preparation and graft size linked to post-op descemetorhexis disparity - Parekh, Mohit; Ruzza, Alessandro; Kaye, Abigail; Steger, Bernhard; Kaye, Stephen B.; Romano, Vito (American journal of ophthalmology case reports, 2018)
To report the management of an intraoperative complication during large (9.5 mm) ultra-thin Descemet Stripping Automated Endothelial Keratoplasty (UT-DSAEK) surgery in a patient with a large area of dysfunctional endothelium. A single case study of an 89 y/o male with a history of Fuchs corneal endothelial dystrophy is presented. The patient was listed for a large UT-DSAEK, but due to an intraoperative complication during graft preparation, an 8.00 mm Descemet membrane endothelial keratoplasty (DMEK) was prepared from the same graft using a standardized SCUBA technique and delivered. Early postoperative examination of the graft showed decentred, residual corneal oedema in the absence of DM detachment and a well-formed anterior chamber. The endothelial graft was found attached after 3 months and the corneal oedema was cleared. After 5 months, the patient's BSCVA was recorded at 6/6(20/20) in the left eye, but complained of mild discomfort. A circular ring of corneal oedema was observed around the graft and decentralization of the transplanted graft was observed. Endothelial cell density (ECD) of the central cornea at 5th month was 1506 cells/mm2 at a focal depth of 496 μm with some polymegathism. and importance: It is possible to prepare DMEK starting from a failed DSAEK graft. Thickness map on corneal tomography could be a useful tool after DMEK for checking graft centration, function, and corneal recovery indirectly. It is recommended to only maintain a small distance between the descemetorhexis area and the size of the endothelial graft.